Improvement of Power in Piezoelectric Energy Harvesting Systems Using the Synchronized Switch Harvesting Inductor (SSHI) Technique - Fikri, M. Ihsanul; Baswara, Ahmad Raditya Cahya (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
Energy needs have always been a problem that must be solved, the utilization of fossil energy sources is a solution that is widely used, but this energy source can run out at any time. The idea to create an energy producer that utilizes mechanical energy from the motion of objects, creating a tool in the form of a floor that can produce electrical energy by utilizing piezoelectricity as a harvester with SSHI technique as an optimizer. Piezoelectric is a sensor that can react when given vibration or pressure. The energy harvesting floor is made using piezoelectrics arranged in series of 16 pieces, this harvesting tool is assisted by standard energy harvesting (SEH) and syncronized swiych harvesting inductor (SSHI) techniques this technique combines several components namely, MOSFET IRF530N, Inductor, reactifier, capacitor. This floor can produce 5V AC energy in a few steps, and produce 2V - 2.5V DC after entering the rectifier, after being given a load in the form of a capacitor and LED the voltage generated per beat is 0.03V - 0.06V, this study compares the harvesting circuit using SSHI and not using SSHI, getting the conclusion SSHI as a harvesting stabilizer dampens the resulting power surge.